A frameshift deletion in the GDF9 gene in Icelandic Loa prolific sheep. (29th December 2021) - Holm, Lars‐Erik; Bendixen, Christian; Eythorsdottir, Emma; Hallsson, Jon H.
Abstract: Several genetic variants have been shown to affect the mean number of offspring in different sheep breeds. Here, we analyzed samples from Icelandic sheep with the aim of identifying the genetic cause of the Icelandic Loa phenotype using three previously identified prolificacy genes as candidates. We demonstrate that a 4‐bp frameshift deletion positioned in the mature region of the GDF9 protein in the Loa animals is a likely causal mutation for the observed increase in prolificacy; however, sequencing showed that not all ewes with a high number of offspring carried the deletion, suggesting the presence of a second mutation segregating within this group of animals.